1993
DOI: 10.3168/jds.s0022-0302(93)77432-9
|View full text |Cite
|
Sign up to set email alerts
|

Teat Tissue Reactions to Milking: Effects of Vacuum Level

Abstract: Machine-induced changes in diameter, thickness, and compressibility of the teat apex and teat barrel were measured on all teats of four cows milked at vacuums of 25, 30, 40, and 50 kPa. Measurements were made with an electronic caliper instrument immediately before milking and then at .5, 15, and 30 min after milking. Teat length was also measured at these times. Immediately after milking, for the two higher levels, teats were significantly thicker (7 to 10% thicker at 40 kPa, 17 to 25% at 50 kPa), shorter (by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 7 publications
5
58
1
2
Order By: Relevance
“…In cows Hamann and Mein (1990) found an increase in TEWT after milking that was 2% at 30 kPa, 8% at 50 kPa and 21% at 70 kPa. Later, Hamann et al (1993) also found that the teats of cows were significantly thicker in higher vacuum levels. On the contrary, Le Du and Taverna (1989) found in cows that the TEWT after milking was lower than that observed before milking.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In cows Hamann and Mein (1990) found an increase in TEWT after milking that was 2% at 30 kPa, 8% at 50 kPa and 21% at 70 kPa. Later, Hamann et al (1993) also found that the teats of cows were significantly thicker in higher vacuum levels. On the contrary, Le Du and Taverna (1989) found in cows that the TEWT after milking was lower than that observed before milking.…”
Section: Discussionmentioning
confidence: 92%
“…In the mountainous Greek breed of ewes (Boutsiko), Sinapis et al (2007) found a slight increase in TEWT (0.63%), while Marnet et al (1999) and Peris et al (2003a,b) found thinner teats after milking in Lacaune and Manchega sheep breeds, respectively. The above results suggest an influence of machine settings and especially of too high vacuum level applied to the teat (Hamann et al, 1993) as well as of the teat cup liner design and characteristics (Le Du and Taverna, 1989). The liner design appears to have a bigger effect on the teat tissue changes than pulsation characteristics or vacuum level (Gleeson et al, 2004).…”
mentioning
confidence: 99%
“…In dairy cows, faulty design of the claw and improper setting of machine milking can cause increasing levels of somatic cell count and intramammary infections by altering the local defense mechanisms of teats and udders against pathogen agents (Hamann et al 1993). Lowering the milking vacuum level is a way to reduce aggression of teat tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Esses dados demonstram que a obstrução do seio lactífero, a partir de lesões na mucosa da PPSL, é rápida e possui diferentes níveis de gravidade, tendo como conseqüência a redução da produção de leite e o aumento do descarte de vacas em rebanhos leiteiros (Roine, 1975). A vasta irrigação oriunda do tecido conectivo frouxo que une a mucosa do seio lactífero às camadas musculares, favorece a proliferação tecidual que invade a PPSL, em casos de extensa lesão na mucosa da papila mamária (Hull, 1995), havendo aumento das reações teciduais na papila mamária quando submetida à ordenha mecânica (Hamann et al 1993). Tabela 2.…”
Section: Resultsunclassified